Developing Higher Order Thinking Skills: Towards a Rethinking of EFL Coursebooks in Moroccan High Schools - Isam Mrah (Yayasan Visi Intan Permata, 2017)
The ever-growing realm of education underlines the need for a reconsideration of learning materials. The present study aimed to investigate the extent to which EFL textbooks in Morocco help learners build skills in accordance with the twenty first century learning expectations. It attempted to assess the effectiveness of Ticket to English textbook series in terms of how well they foster critical thinking and problem solving among learners. The study adopted content analysis as the primary research method for data analysis and interpretation. The analysis was undertaken to define the types and levels of questions addressed in reading comprehension tasks and to examine instances of higher order thinking skills. The case study evaluated the questions in the light of the Bloom's Revisited Taxonomy of learning objectives. Results from the content analysis of questions show that most of the questions targeted the three lower-level categories of the taxonomy. The results obtained testify that the examined textbooks do not effectively enable learners to be autonomous lifelong critical thinkers, hence the need for a reconsideration of EFL textbooks in Moroccan high schools. The paper eventually suggests some ways in which these skills could be promoted effectively in future textbooks with the aim of empowering students to thrive in an evolving world.